2015
DOI: 10.1128/jvi.03532-14
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Adaptive Mutations of the PA Protein of Highly Pathogenic Avian H5N1 Influenza Virus

Abstract: Highly pathogenic H5N1 influenza A viruses continue to circulate among avian species and cause sporadic cases of human infection. Therefore, the threat of a pandemic persists. However, the human cases of H5N1 infection have been limited mainly to individuals in close contact with infected poultry. These findings suggest that the H5N1 viruses need to acquire adaptive mutations to gain a replicative advantage in mammalian cells to break through the species barrier. Many amino acid mutations of the polymerase com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Previously, some mutations in the PA protein were reported for their association with mammalian adaptation of H5N1 viruses2829. These mutations increased viral replication capacity in cells and pathogenicity in mice via interactions with other amino acid signatures in the same PA or other viral proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, some mutations in the PA protein were reported for their association with mammalian adaptation of H5N1 viruses2829. These mutations increased viral replication capacity in cells and pathogenicity in mice via interactions with other amino acid signatures in the same PA or other viral proteins.…”
Section: Resultsmentioning
confidence: 99%
“…25,26 In terms of etiology, our report showed that no significant mutation was observed to be associated with enhancing the transmission or increasing human adaption in the genomic sequence according to previous studies including receptor binding sites in the HA or NA genes, [27][28][29][30] enhancing replication ability-associated sites, [31][32][33] or enhancing pathogenic-associated sites. 34 However, etiological surveillance has shown that the virus has presented continuous mutations since emerging in 2013 6 , suggesting that the largest outbreak of wave V may be due to a constellation of genes rather than a single mutation. 35 In addition, genetic drift evolution of avian influenza virus has been associated with vaccination pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The amino acids at positions 343 and 347 of PA had been reported to affect influenza virus replication (34,(41)(42)(43)(44), but these studies did not assess the particular amino acid changes tested here and did not evaluate the combined effect of PA-343/ 347 on influenza virus replication and pathogenicity. Previously, we reported that the PA gene of a human H5N1 influenza virus (A/Vietnam/UT36285/2010) increased the polymerase activity and mouse virulence of an avian H5N1 influenza virus (A/chicken/ Vietnam/TY31/2005) (34). Further studies identified five amino acid residues in PA, among them PA-343T, that contributed to the increased replication and virulence of the reassortant virus (34).…”
Section: Discussionmentioning
confidence: 99%
“…The third subunit of the influenza virus polymerase complex, PA, encodes an endonuclease that cleaves the cap structure and subsequent nucleotides from cellular mRNA to generate primers for influenza viral transcription (reviewed in reference 40). As for PB1 and PB2, several studies have identified amino acid positions in PA (including PA-44, PA-101, PA-127, PA-185, PA-224, PA-237, PA-241, PA-343, PA-347, PA-353, PA-383, and PA-573) that affected replication and/or virulence (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(41)(42)(43)(44).…”
mentioning
confidence: 99%